URO: urología relevante y objetiva. Narrativa transmedia para la prevención del cáncer urológico - Ismael Cardozo-Rivera; Herney A. García-Perdomo (Urología Colombiana)
Objective: UOR is a transmedia project carried out between the Narratives and Digital Journalism hotbed of the Universidad Autónoma de Occidente and the UROGIV research group of the Universidad del Valle, which was born from the research-creation objective of developing a transmedia narrative. This project would make it possible to contribute to the prevention of urological cancer, using the knowledge and the different investigations of the urology research group at the service of the community. Method: For this, a methodology was carried out that included a search, classification and selection of the papers advanced by UROGIV, the formulation of a model for the URO transmedia narrative and finally its evaluation based on the scope of the proposal in digital media and the analysis in its realization process. Results: A series of contents such as podcasts, video-documentaries and infographics were generated, socialized through the Spotify, Instagram, Facebook and YouTube platforms. In addition, a web repository that would allow uniting all the proposals of the project. Fifty-one communicative products were made. Instagram had follower accounts and interactions that allowed the platform to be evaluated positively. Conclusion: The development of this transmedia narrative showed as conclusions the importance of carrying out initiatives of this nature, and of adapting publications in urology to a more common language, in order to achieve a greater reach in terms of audience.